Attitude towards English Slogan Used by Culinary Products of SMES and How It Affects Purchase Decisions - Gartika Rahmasari; Wawan Hendrawan (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This study examines the perception and comprehension of consumers towards 6 English slogans used by SMEsâ€™ culinary product, particularly fruit-based crackers. Slogans examined include Aruna ( â€œOriginal taste and crispyâ€), Jecko ( â€œSo crunchy), Matoh ( â€œGood things come to those who shareâ€), Miun Chips ( â€œIndonesian sweet cassava chipsâ€), Paradis Crunch (â€œPremium Indonesian banana chipsâ€), and Zanana ( â€œTry it; Love it; Miss it.â€). As a result, the most easy to understand English slogan considered by respondent is Aruna (â€œOriginal taste and crispyâ€) as much as 96,2%, and the most difficult slogan to understand is Matoh (â€œGood things come to those who shareâ€) as much as 34,6%. In addition, slogans considered to be the easiest translated are Aruna and Zanana, where 100% of respondents stated that they were able to translate both slogans. However, when they were asked to translate all 6 slogans, it is slogan of Jecko which could be translated correctly by most, as much as 86,4%, and the most difficult slogan to translate is the slogan of Miun Chips. Also, Jecko has the slogan whose meaning is well understood by most of respondents, as much as 88,5 % respondents, and the slogan whose meaning is the most difficult to understand is the slogan of Miun Chips (30,8%). This study concluded that the use of English slogans by SMEsâ€™ culinary product, despite how easy or difficult they are to be understood, did not affect buying decision. It is the package (46,2 %) and the taste of product (34,6%) that become the main reason for consumers to make buying decision, besides the price (15,4%) and halal sertificate (3,8%). Keywords: English Slogan, Purchase Decision, SME